2020
DOI: 10.1108/pr-07-2019-0399
|View full text |Cite
|
Sign up to set email alerts
|

The voicer's reactions to voice: an examination of employee voice on perceived organizational status and subsequent innovative behavior in the workplace

Abstract: PurposeThe purpose of this paper was to explore the voicer's own psychological or behavioral reactions to voice. A framework was proposed to predict how and when employee voice is related to innovative behavior in the workplace based on conservation of resources theory.Design/methodology/approachData was collected from a three-wave survey including 232 employees and their supervisors. Hierarchical multiple regression and PROCESS, a SPSS macro, were used to test the hypotheses.FindingsEmployee voice was positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 86 publications
1
22
0
1
Order By: Relevance
“…Inspired by prior research, we controlled employees' demographic characteristics, including gender, age and education in the present study, allowing for their influences on innovative behavior to be reflected in the findings (Eva et al, 2019;Pian et al, 2019;Chen et al, 2020). In addition, we included job type of focal employees as a control variable since prior research noted that job type was associated with employees' creativity (Tsaur et al, 2011).…”
Section: Control Variablesmentioning
confidence: 99%
“…Inspired by prior research, we controlled employees' demographic characteristics, including gender, age and education in the present study, allowing for their influences on innovative behavior to be reflected in the findings (Eva et al, 2019;Pian et al, 2019;Chen et al, 2020). In addition, we included job type of focal employees as a control variable since prior research noted that job type was associated with employees' creativity (Tsaur et al, 2011).…”
Section: Control Variablesmentioning
confidence: 99%
“…Voice behavior is an important factor that can improve organizational efficacy (Chen et al, 2020a). Many theoretical perspectives have been used to explore the antecedents of voice behavior, such as leader–member exchange (Burris et al, 2008), climate (Morrison et al, 2011), proactive personality (Wijaya, 2019), and voice efficacy (McAllister et al, 2007).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Therefore, it is inferred that communication visibility might be conducive to employee voice behavior. Further, Chen et al (2020a) showed that voice behavior facilitated idea generation and that the resources accompanied by voice behavior were conducive to turning employees’ suggestions into actual innovative behaviors. Therefore, this study examines the mediating effect of voice behavior to explain how communication visibility affects innovation behavior.…”
mentioning
confidence: 99%
“…One of the most important aspects of employees' life is the safety voice (a dimension of safety behavior, defined as one's propensity to raise voice for unsafe practices at work) (Tucker and Turner, 2011). Employees' voice has been valued at work as it is found to direct the organizational efforts toward areas of improvement (Chen et al , 2020; Chillas and Marks, 2020; King et al , 2020), especially in crisis (Lee, 2020). As COVID-19 has also a crisis that has settled new normals for businesses and firms have to transform their practices (Breier et al , 2021; Seetharaman, 2020), it is expected that the employee's voice for safety would have greater significance in current pandemic crisis.…”
Section: Introductionmentioning
confidence: 99%